Patient interpretations of patient-reported outcome measures to assess bowel urgency: qualitative interviews in ulcerative colitis - Jairath, V; Gibble, TH; Moses, R; Klooster, B; Litcher-Kelly, L; Walker, M; Bernstein, MC; Rupinski, K; McLafferty, M; Travis, S; Dubinsky, M (SpringerOpen, 2024)
Objectives: Bowel urgency is an impactful core symptom of ulcerative colitis (UC). Patient-reported outcome (PRO) questionnaires have been developed and used to assess the patient experience of this important symptom. The objective of this paper is to present evidence from qualitative research conducted to support the use and interpretation of select PRO questionnaires to assess bowel urgency related to the UC patient experience. Methods: Qualitative interviews were conducted with ten adults with a clinician-confirmed diagnosis of moderately to severely active UC. Interviews aimed to document patient interpretation of modified recall periods for the Urgency Numeric Rating Scale (Urgency NRS), two global assessments (i.e., the Patient Global Impression of Severity [PGIS] and Patient Global Impression of Change [PGIC]), and four items (Items 11, 16, 23, and 26) of the Inflammatory Bowel Disease Questionnaire (IBDQ), and explore the patient perspective of meaningful change on these questionnaires. Results: Both modified Urgency NRS versions (with 7-day or 3-day recall period) were interpreted as intended by most patients (≥ 88.9%), and slightly more than half of patients (60.0%) reported that the 7-day recall period was more relevant to their bowel urgency experience. Patients reported thinking of bowel urgency (≥ 80.0%) or bowel urgency-related accidents (70.0% of patients) when interpreting the global assessments and IBDQ items. Most patients reported a 1- to 3-point change as the smallest meaningful improvement that would be meaningful on the Urgency NRS (similar to findings on other questionnaires). Conclusion: Adults with UC can understand and respond to the Urgency NRS with modified recall periods (i.e., 7-day or 3-day), interpret the conceptual content of the PGIS, PGIC, and select IBDQ items to be inclusive of bowel urgency and bowel urgency-related accidents, and select answers representing meaningful improvements on the Urgency NRS, PGIS, PGIC, and IBDQ item response scales. These results further contribute patient-centered data to existing UC and bowel urgency research.